MiR-4310 induced by SP1 targets PTEN to promote glioma progression - Wu, Zhiyong (Cancer Cell Int, 2020)
BACKGROUND: miRNAs have been reported to be involved in multiple biological processes of gliomas. Here, we aimed to analyze miR-4310 and its correlation genes involved in the progression of human glioma. METHODS: miR-4310 expression levels were examined in glioma and non-tumor brain (NB) tissues. The molecular mechanisms of miR-4310 expression and its effects on cell proliferation, migration, and invasion were explored using 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide, Transwell chamber, Boyden chamber, and western blot analyses, as well as its effect on tumorigenesis was explored in vivo in nude mice. The relationships between miR-4310, SP1, phosphatase, and tensin homolog (PTEN) were explored using chromatin immunoprecipitation, agarose gel electrophoresis, electrophoresis mobility shift, and dual-luciferase reporter gene assays. RESULTS: miR-4310 expression was upregulated in glioma tissues compared to that in NB tissues. Overexpressed miR-4310 promoted glioma cell proliferation, migration, and invasion in vitro, as well as tumorigenesis in vivo. The inhibition of miR-4310 expression was sufficient to reverse these results. Mechanistic analyses revealed that miR-4310 promoted glioma progression through the PI3K/AKT pathway by targeting PTEN. Additionally, SP1 induced the expression of miR-4310 by binding to its promoter region. CONCLUSION: miR-4310 promotes the progression of glioma by targeting PTEN and activating the PI3K/AKT pathway; meanwhile, the expression of miR-4310 was induced by SP1.